Effects of Controlled Cortical Impact and Docosahexaenoic Acid on Rat Pup Fatty Acid Profiles - Schober, Michelle E. (Behav Brain Res, 2019)
Traumatic brain injury (TBI) is the leading cause of acquired neurologic disability in children, particularly in those under four years old. During this period, rapid brain growth demands higher Docosahexaenoic Acid (DHA) intake. DHA is an essential fatty acid and brain cell component derived almost entirely from the diet. DHA improved neurologic outcomes and decreased inflammation after controlled cortical impact (CCI) in 17-day old (P17) rats, our established model of pediatric TBI. In adult rodents, TBI decreases brain DHA. We hypothesized that CCI would decrease rat brain DHA at post injury day (PID) 60, blunted by 0.1% DHA diet. We quantitated fatty acids using Gas Chromatography–Mass Spectrometry. We provided 0.1% DHA before CCI to ensure high DHA in dam milk. We compared brain DHA in rats after 60 days of regular (REG) or DHA diet to SHAM pups on REG diet. Brain DHA decreased in REGCCI, not in DHACCI, relative to SHAMREG. In a subsequent experiment, we gave rat pups DHA or vehicle intraperitoneally after CCI followed by DHA or REG diet for 60 days. REG increased brain Docosapentaenoic Acid (n-6 DPA, a brain DHA deficiency marker) relative to SHAMDHA and DHACCI pups (p<0.001, diet effect). DHA diet nearly doubled DHA and decreased n-6 DPA in blood but did not increase brain DHA content (p<0.0001, diet effect). We concluded that CCI or craniotomy alone induces a mild DHA deficit as shown by increased brain DPA.